STUDENTS' PERCEPTION OF SIMULATOR USE IN CLINICAL DENTAL PRACTICE AT PERUVIAN UNIVERSITIES - Mezarina-Mendoza , Jhon Paul Iakov (2026)
Introduction: Simulation in dentistry provides controlled environments that replicate clinical situations, allowing students to acquire competencies safely. Although international evidence highlights its benefits, studies in Peru remain scarce. Methods: A cross-sectional descriptive study was conducted with 222 dental students from five Peruvian universities. A validated questionnaire (Aiken’s V=0.906; Cronbach’s α=0.946) assessed didactic utility, competency development, and simulation experience. Results: Most students considered simulators useful for applying theoretical knowledge (79.1%), improving visual and motor skills (72.9%), and increasing clinical confidence (68.8%). Conclusions: Simulators are valuable tools in dental education, strengthening skills and confidence before clinical practice. Their effectiveness could be enhanced by improving supervision and material quality.